A = 2011 x 2010 - 1
_____________
2009 x 2011 - 2010
Tính A
2011 x 2010 - 1/2009 x 2011 + 2010
`(2011xx2020-1)/(2009xx2011+2010)`
`=((2009+1)xx2011-1)/(2009xx2011+2010)`
`=(2009xx2011+2011-1)/(2009xx2011+2010)`
`=(2009xx2011+2010)/(2009xx2011+2010)`
`=1`
\(\dfrac{2011.2010-1}{2009.2011+2010}\)
= \(\dfrac{2011.2009+2011-1}{2009.2011+2010}\)
= \(\dfrac{2011.2009+2010}{2009.2011+2010}\)
= 1
(2009 x 2010 + 2011 x 12 + 1998)/(2011 x 2010 - 2010 x 2009)
Tính : A = 2007 + 2008 x 2009 / 2009 x 2010 - 2011 = ?
A=4036079 : 4036079
A=1> Câu trả lời này đúng
100% đó bạn
Tính : A = 2007 + 2008 x 2009 / 2009 x 2010 - 2011 = ?
tính nhanh A= 4047991- 2010 x 2009/ 4050000-2011 x 2009
\(A=\frac{4047991-2010.2009}{4050000-2011.2009}\)
\(\Rightarrow A=\frac{404791-2010.2009}{4047911+2009-2011.2009}\)
\(\Rightarrow A=\frac{4047911-2010.2009}{4047911-2010.2009}\)
\(\Rightarrow A=1\)
Vậy A = 1
~Study well~
#๖ۣۜNamiko#
#)Giải :
\(A=\frac{4047991-2010.2009}{4050000-2011.2009}=\frac{407991-2010.2009}{4047991+2009-2011-2009}=\frac{407991-2010.2009}{407991-2010.2009}=1\)
#~Will~be~Pens~#
\(\frac{x-2010-2011}{2009}\)+\(\frac{x-2009-2011}{2010}\)+\(\frac{x-2009-2010}{2011}\)= 3
lấy cả 2 vế trừ đi 3
\(\frac{x-2010-2011}{2009}+\frac{x-2009-2011}{2010}+\frac{x-2009-2010}{2011}=3\)
\(\Leftrightarrow\left(\frac{x-2010-2011}{2009}-1\right)+\left(\frac{x-2009-2011}{2010}-1\right)+\left(\frac{x-2009-2010}{2011}-1\right)=0\)
\(\Leftrightarrow\frac{x-6030}{2009}+\frac{x-6030}{2010}+\frac{x-6030}{2011}=0\)
\(\Leftrightarrow\left(x-6030\right)\left(\frac{1}{2009}+\frac{1}{2010}+\frac{1}{2011}\right)\)
\(\Leftrightarrow x-6030=0\)(vì \(\frac{1}{2009}+\frac{1}{2010}+\frac{1}{2011}>0\))
\(\Leftrightarrow x=6030\)
Vậy ................
Bài 1 :
a, A= 2011*2010-1 / 2011*2009+2010
B, Tìm x
1- {11/4+x-5/3} : 19/5 =0
A = 2011 x (2009 + 1) - 1/ 2011 x 2009 + 2010
A = 2011 x 2009 + 2011 x 1 - 1/2011 x 2009 + 2010
A = 2011 x 2009 + 2010/2011 x 2009 + 2010
A = 1
B.
So sánh :
A = 2009/2010 + 2010/2011 + 2011/2012
B = 2009 + 2010 + 2011/2010 + 2011 + 2012
Có : \(2009+2010>\dfrac{2009}{2010}\) ; \(2011+2012>\dfrac{2011}{2012}\)
\(\dfrac{2011}{2010}>1\) ; \(\dfrac{2010}{2011}< 1\) \(\Rightarrow\dfrac{2011}{2010}>\dfrac{2010}{2011}\)
Ta có : \(2009+2010+\dfrac{2011}{2010}+2011+2012>\dfrac{2009}{2010}+\dfrac{2010}{2011}+\dfrac{2011}{2012}\)
\(\Leftrightarrow B>A\)
Hay \(A< B\)
1 / 1 + 2009 / 2010 + 2009 / 2011 + 1 / 1 + 2000 / 2009 + 2010 / 2011 + 1 / 1 + 2011 / 2009 + 2011 /2010